PORTRAYING THE WABI SABI PHILOSOPHY OF BEAUTY IN KAWABATA’S SNOW COUNTRY - Cahyaningati, Desi Tri (Jurnal Sastra dan Budaya Dinamika, 2018)
AbstractSnow country depicts beauty of nature, people, and love through the characters and the situation with the elements of sincerity, purity, calmness and condusiveness. Beauty itself is one of the major themes in this novel. However, Kawabata has his own perception of the beauty that is different with common perception of beauty. Therefore, this paper aims to investigate the philosophy of beauty in Kawabata’s Snow Country. These beauty were analyzed through philosophical point of beauty by Kant and Japanese aesthetic philosophy wabi sabi. In fact, the writer found that almost all of beauty in snow country included the sad element, such as a loneliness in a beauty of nature,  sadness in a beautiful voice and a waste effort in a beauty of love. The beauty of unusual, imperfect (Wabi Sabi) was found in the way Kawabata depicted the beauty of the women in this novel; Komako and Yoko. Keywords: Philosophy, Beauty, Wabi Sabi, Snow Country, Kawabata